Isolated Splenic Vein Thrombosis: 8-Year-Old Boy with Massive Upper Gastrointestinal Bleeding and Hypersplenism - Mohammad Ali Kiani; Arash Forouzan; Kambiz Masoumi; Behnaz Mazdaee; Mohammad Bahadoram; Hamid Reza Kianifar; Hassan Ravari (Case Reports in Pediatrics)
We present an 8-year-old boy who was referred to our center with the complaint of upper gastrointestinal bleeding and was diagnosed with hypersplenism and progressive esophageal varices. Performing a computerized tomography (CT) scan, we discovered a suspicious finding in the venography phase in favor of thrombosis in the splenic vein. Once complementary examinations were done and due to recurrent bleeding and band ligation failure, the patient underwent splenectomy. And during the one-year follow-up obvious improvement of the esophageal varices was observed in endoscopy.